Licocalchone-C Extracted from Glycyrrhiza Glabra Inhibits Lipopolysaccharide-Interferon-γ Inflammation by Improving Antioxidant Conditions and Regulating Inducible Nitric Oxide Synthase Expression - Franceschelli, Sara (Molecules, 2011)
The genus Glycyrrhiza consists of about 30 species, amoung these, G. glabra is the source of several phenolic compounds, known as flavonoids, such as licoagrodin, licoagrochalcones, licoagroaurone and licochalcone C, kanzonol Y, glyinflanin B and glycyrdione A, which have shown various pharmacological activities, including antitumor, antiparasitic, antileishmanial, anti-ulcer and antioxidative effects. Among these compounds, licochalcone C was isolated but its biology has not been fully examined. In our study we reproduced an inflammatory state by treating THP-1 (human myelomonocytic leukaemia) cells with pro-inflammatory stimuli, such as LPS and IFN-γ and we investigated the possible antioxidant activity of licochalcone C at a concentration of 50 μM. Our results show that treatment with licochalcone C attenuates the LPS-IFN-γ-induced inflammatory response by significantly decreasing the expression and activity of iNOS via NFκB (nuclear factor kappa-B), by influencing extracellular O(2)(−) production, and by modulating the antioxidant network activity of SOD (superoxide dismutase), CAT (catalase) and GPx (glutathione peroxidase) activity. Based on these results we hypothesize that Licochalcone C has antioxidant properties since it reduces the production of superoxide radicals and consequently reduces the activity of iNOS.